Global urbanism Knowledge, Power and the City (Taylor & Francis, 2021)
Eastern Europe, activism, housing, urban policies, urban power structures, spacial justice, global urbanism
English
Keywords: Human geography; Society & culture: general; Urban communities; Eastern Europe, activism, housing, urban policies, urban power structures, spacial justice, global urbanism